2020
DOI: 10.1093/eurheartj/ehz893
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade endotoxaemia enhances artery thrombus growth via Toll-like receptor 4: implication for myocardial infarction

Abstract: Aims Low-grade endotoxaemia is detectable in human circulation but its role in thrombosis is still unclear. Methods and results We measured serum lipopolysaccharide (LPS) concentration, soluble P-selectin (sP-selectin), a marker of platelet activation, and zonulin, a marker of gut permeability, in peripheral circulation, coronary thrombi, and intracoronary blood of patients with ST-elevation myocardial infarction (STEMI, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 29 publications
3
92
0
Order By: Relevance
“…12,80 Increasing evidences suggest that LPS and/or neutrophil activation could play a role also in cancer, [81][82][83] in asthma, 8,9 and in cardiovascu-lar disorders. 7 All these conditions are associated with altered production of angiogenic factors. 33,34,70,71 Therefore, the possibility cannot be excluded that the modulation by cannabinoids of angiogenic factors released by neutrophils might have novel therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,80 Increasing evidences suggest that LPS and/or neutrophil activation could play a role also in cancer, [81][82][83] in asthma, 8,9 and in cardiovascu-lar disorders. 7 All these conditions are associated with altered production of angiogenic factors. 33,34,70,71 Therefore, the possibility cannot be excluded that the modulation by cannabinoids of angiogenic factors released by neutrophils might have novel therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the last decades this view has been challenged due to recent evidences indicating that neutrophils survival time is significantly longer than the lifespan usually reported (<1 d) 2 and they produce a variety of cytokines and chemokines, 3 lipid mediators, angiogenic factors, 4 and neutrophil extracellular traps. 5 There is now evidence that PMNs play a role in several chronic inflammatory disorders, 6 cardiovascular diseases, 7 asthma, 8,9 tumors, 4,10 sepsis, 11,12 and parasitic diseases. 13 To exert their functions, PMNs express a plethora of immunoreceptors, including TLRs 14 and endocannabinoids receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we observed that E. coli caiTABCDE operon genes (encoding for membrane transport and metabolism of L-Carnitine to γBB and TMA [ 15 , 19 ]) were overrepresented in subjects with +IMT/ +SCA (see Supplementary Materials, Figure S5 ). Carnevale et al [ 62 ] recently showed higher E. coli abundance in GM of patients with STEMI, correlating to increased systemic Lipopolysaccharide (LPS) absorption and infiltration in atheromas from endarterectomies leading to macrophage activation [ 48 ]. In our investigation, we did not find increased plasma levels of zonulin in +IMT/+SCA subjects (see Supplementary Figure S6 ), therefore prompting the exclusion of systemic LPS absorption through a “leaky-gut” [ 63 ] yet at initial stages of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The term “low-grade endotoxemia” or “metabolic endotoxemia” was recently coined for a better representation of subclinically elevated levels of circulating blood endotoxin. It has been speculated that circulating endotoxins, usually attributed to the translocation of gut-microbiota-derived LPS from the gastrointestinal tract into the bloodstream, can cause or exacerbate chronic inflammatory diseases, to which inflammation-related diseases such as ischemic heart disease, stroke, cancer, diabetes mellitus, chronic kidney disease, nonalcoholic fatty liver disease (NAFLD), and autoimmune and neurodegenerative conditions are attributable [ 66 , 67 , 68 , 69 ]. Several studies have reported the relationship between low-grade endotoxemia and metabolic diseases such as insulin resistance and obesity [ 66 , 70 , 71 ].…”
Section: Low-grade Endotoxemia Related To Chronic Inflammationmentioning
confidence: 99%
“…Replacement of the LAL test used in these studies with the endotoxin-specific LAL assay should make the data more reliable and valid. Additionally, an alternative method using ELISA for the detection of low-grade endotoxemia can be used to determine gut permeability and bacterial translocation, although its sensitivity and specificity relative to the LAL assay are unknown [ 69 ]. More interestingly, Finkelman et al suggested that the detection of (1→3)-β-D-glucanemia rather than endotoxemia may serve as a novel biomarker for fungal translocation into systemic circulation and improve the understanding of leaky gut syndrome [ 72 ].…”
Section: Low-grade Endotoxemia Related To Chronic Inflammationmentioning
confidence: 99%